PENGARUH PAD DAN BELANJA MODAL TERHADAP TINGKAT KEMISKINAN DAN IPM DI KABUPATEN/KOTA PROVINSI BALI - Sugion, I Putu Gede France; Purbadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 1 (2021): VOL 10 NO 1, JANUARI 2021 [ 1 - 450 ], 2021)
The regional government policies have issued expected able to overcome ongoing problems, they can improve standard of living of people, for example utilizing PAD used as capital expenditure which is expected to provide long-term benefits for the community. The research objectives were to analyze (1) effect PAD and capital expenditures on poverty levels regencies / cities Bali province. (2) effect PAD, Capital Expenditures and Poverty Levels on IPM Regency / City Bali Province. (3) PAD and Capital Expenditures on the IPM through the Poverty Level Regency / City Bali Province. Analysis technique uses path analysis. Results of the study are (1) local revenue and capital expenditure directly have a negative (significant) effect on poverty levels in the regencies / cities of Bali Province. (2) Local original income and capital expenditure do not directly have a significant effect on the human development index, while the poverty level directly has a negative (significant) effect on the human development index in the regencies / cities of Bali Province. (3) Local revenue and capital expenditure indirectly affect the Human Development Index through the Poverty Level in the Regency / City of Bali Province.   Key words: local revenue, capital expenditure, poverty rate, human development index.